2015
DOI: 10.5944/reec.26.2015.14447
|View full text |Cite
|
Sign up to set email alerts
|

Tranformaciones en la universidad hoy: integración de modalidades formativas

Abstract: The introduction and intensive use of ICTs, and the internet in particular, have led to important changes at universities over the last three decades. Technologies have transformed people's skills and lives and they have transformed organizations too. This article reviews the most important changes at universities that have affected all the members of the education community: students, faculty and administration. It analyses the transformations in pedagogy, in the use of technology and in university management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In fact, there is no single model that can be used definitively in training, either for university classes or for educators. Higher education institutions are faced with new hybrid models, which integrate face-to-face and virtual classes thanks to the possibilities technology offers [65]. This became even more evident in this first half of 2020, due, unfortunately, to the Covid-19 health pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is no single model that can be used definitively in training, either for university classes or for educators. Higher education institutions are faced with new hybrid models, which integrate face-to-face and virtual classes thanks to the possibilities technology offers [65]. This became even more evident in this first half of 2020, due, unfortunately, to the Covid-19 health pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…the non-significant direct effect of instructor quality and system quality on continuance commitment), one possible explanation might be the transcendental change in the educational paradigm, especially reflected in e-learning education. Teachers have to manage the design of their courses and are in charge of monitoring the learning process, but they play the role of facilitators rather than authorities (Duart and Mengual-Andrés, 2015). These results reinforce the need for a new conceptualization of the figure of the teacher in the e-learning context (McConnell, 2018), as neither students nor teachers found that their continuance commitment was significantly influenced by the perceived quality of the instructor.…”
Section: Discussionmentioning
confidence: 73%
“…There is a consensus among scholars over the need to combine technological progress with learning models of proven utility to each educational community and society (Barajas, 2002;Duart and Mengual-Andrés, 2015). E-learning success often depends on the implementation of a pedagogical model that is focused on matching the objectives and the necessities of both students and teachers (Bartolomé and Aiello, 2006;Lee, et al, 2009), rather than seeking to cultivate other institutional interests.…”
Section: E-learning In the Context Of Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…La integración y uso intensivo de tecnologías digitales, en particular basadas en la web están transformando las universidades en todo el mundo (Duart & Mengual, 2015;Boelens et al, 2018;Dziuban, et al, 2018). Las institucio-nes de educación superior han incorporado las plataformas tecnológicas ricas en medios para la evaluación, así como los "cursos personalizados o adaptativos y las herramientas de conferencia web, capaces de conectar a los estudiantes para actividades a distancia sincrónicas, se están convirtiendo en soluciones comunes para los diseños de aprendizaje blended learning (BL)" (Alexander et al, 2019, p. 12), pues la tecnología tiene el potencial de aumentar el acceso a la educación, mejorar las experiencias de aprendizaje y reducir el costo de proporcionar educación postsecundaria de alta calidad (Protopsaltis & Baum, 2019).…”
Section: Introductionunclassified